Yield and nutrient composition of forage crops and their effects on soil characteristics of winter fallow paddy in South China - Xu, Liuxing; Tang, Guojian; Wu, Dan; Zhang, Jianguo (Frontiers in Plant Science, 2024)
In terms of providing additional feeds and improving the soil fertility, planting forage crops during the fallow seasons is an effective strategy to promote resource utilization. The objective of this research was to compare the effects of planting different forage crops on the yields and nutritive compositions of forage and soil properties of winter fallow paddy in southern China. Five forage crops, including alfalfa (Medicago sativa, AF), common vetch (Vicia sativa, CV), milk vetch (Astragalus sinicus, MV), smooth vetch (Vicia villosa, SV) and Italian ryegrass (Lolium multiflorum, IR), were planted by monoculture on the winter fallow paddy in 2017-2018 (season 1) and 2018-2019 (season 2), respectively. The dry matter yield of IR was significantly higher than those of AF, CV, SV and MV (P<0.05). The crude protein yield of IR was significantly higher than those of AF, CV and MV (P<0.05). The neutral detergent fiber and acid detergent fiber contents of CV, SV and IR were significantly lower than those of AF and MV (P<0.05). Forage crops significantly affected the culturable microbial population of soils (P<0.05). The bacteria, actinomyces and fungi numbers on IR were the highest, while azotobacter number was the lowest. The catalase, acid-phosphatase and invertase activities of IR soil were the lowest. The numbers of bacteria, actinomyces and fungi of IR soil were the highest. IR and SV were the best crops to obtain forage and improve the soil. When producers pursue higher forage yield, we recommend planting Italian ryegrass. If the producers want to improve soil characteristics, smooth vetch is the most suitable plant. These results provide useful information to rice growers for cropping management when growing forage crops (based on the yield and nutritional value) or green manure (based on improving the soil fertility) as an alternative to late rice harvest.